Understanding and controlling defects in quantum confined semiconductor systems - Luo, Hongfu (Kansas State University, 2016)
Semiconducting nanoparticles have emerged in the past few decades as an interesting material with great potential in various interdisciplinary applications such as light-emitting devices, solar cells and field-effect transistors, mostly notably for their size-dependent electronic structure and properties. Manipulation of their electronic-optical characters through defects control is one of the most important approaches towards realization of these applications. This thesis focuses on understanding the role of defects, including their impact on carrier density and conductivity at both room and elevated temperature, their impact on growth kinetics of colloidal nanoparticles and new opportunities for dopant control. To achieve these goals, colloidal CdSe quantum dots are doped with gallium atoms and important changes in electronic and optical properties of the material are reported, which shows a significant impact on the growth kinetics of quantum dots, and reveals clues about the mechanism of the gallium dopant incorporation into the CdSe. It is shown that the gallium doping significantly impacts the conductivity of CdSe thin film made of the quantum dots as well as the photoluminescence and chemical reactivity of the quantum dots, in agreement with the expected n-type character. P3HT/CdSe hybrid cells are constructed with Ga-, In- and Sn-doped CdSe QDs, demonstrating high conductivity and stronger electronic coupling which leads to enhanced charge separation and transport efficiency, both essential for hybrid inorganic-organic solar cells. This work also demonstrates a novel heating method that can drastically improve size distribution control of colloidal nanoparticle synthesis. Sub-2-nm ultra-small CdSe QDs are prepared with the induction (magnetic) heating and show excellent agreement of its emission profile compared with natural sunlight. The impact of extreme high heating rate on the development of more accurate nucleation and growth theories are also discussed. Finally, this study also investigates the stabilization of charges from intrinsic defects by looking for altered blinking behaviors of CdSe nanorods (NRs) under different polar environments. TMOS-PTMOS gradient films are prepared with infusion withdrawal dip-coating technique. Although no significant differences are observed of the fluorescence statistics of these NRs, permanent bleaching induced by exciting laser light is discovered, which significantly lowers raw blinking spot count and increases the “off” time of these fluorophores.
Keywords: doping; quantum dot; CdSe; solar cell; induction heating